Pengaruh Likuiditas, Leverage Dan Perputaran Modal Kerja Terhadap Profitabilitas - Dara Putri Junianti; Ai Hendrani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Profitability is a measure of the success of a company based on the efficiency of capital use. This ratio can prove the company's level of efficiency in generating profits. The aim of this research is to observe the comparison between variables on profitability, determine the influence between variables on profitability and to analyze the influence of liquidity, leverage and working capital turnover on profitability in the food and beverage sub-sector in 2020 - 2022. The research model uses a causal design model and use the proposed sampling method to analyze data from secondary panel data. In the period 2020 to 2022, 108 data were collected from 36 food and beverage companies. The research results show that leverage (DER) has a negative impact, liquidity (CR) and working capital turnover have a positive impact on profitability (ROA), while liquidity (CR) has a significant negative impact on profitability (ROA), leverage (DER) has a significant negative impact on profitability (ROA) and working capital turnover (WCTO) have no impact on profitability (ROA). Keywords: Profitability, Liquidity, Leverage and working capital turnover